1998
DOI: 10.1111/1467-9566.00094
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Hospice Care: the Sequestration of the Unbounded Body and ‘Dirty Dying’

Abstract: This paper is based on a 10-month participant observation study within an inpatient hospice in Southern England. I highlight the difficulties of using homogenous categories such as 'the dying patient' and 'the dying process' in exploring the marginalisation of patients within the physical space of contemporary hospices and similar institutions. In opposition to such categories, my findings indicate the importance of focusing upon the body of the patient, and the disease processes taking place within it and upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
1
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(172 citation statements)
references
References 7 publications
1
163
1
6
Order By: Relevance
“…In relation to uncontrolled symptoms and wounds that leaked Lawton (1998) observed how patients who experienced the break down in the surface of their bodies from wounds and other problems, exhibited a loss of self and social identity when their bodies became irreversibly unbounded. Although palliative care seeks to palliate the unbounded body and where possible enable the bounding of the wound there is evidence from a number of studies that this group of patients with malignant wounds receive inadequate specialised professional help in relation to palliation of the fungating wound (Lo et al 2008;Probst 2010) The aim of the research reported in this article is to explore the experiences of women with a malignant fungating breast wound living in the community in Switzerland.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In relation to uncontrolled symptoms and wounds that leaked Lawton (1998) observed how patients who experienced the break down in the surface of their bodies from wounds and other problems, exhibited a loss of self and social identity when their bodies became irreversibly unbounded. Although palliative care seeks to palliate the unbounded body and where possible enable the bounding of the wound there is evidence from a number of studies that this group of patients with malignant wounds receive inadequate specialised professional help in relation to palliation of the fungating wound (Lo et al 2008;Probst 2010) The aim of the research reported in this article is to explore the experiences of women with a malignant fungating breast wound living in the community in Switzerland.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…An intolerance of the disintegrating and decaying body is a feature of Western society, which demands the removal of such a body from view. Lawton (1998) describes how such bodies are often found in the hospicewhich provided a space of mediation between the bounded and unbounded body (Lawton 1998). For Linda she was fearful of going out with only one breast and a wound that leaks.…”
Section: Being So Unpredictablementioning
confidence: 99%
“…Det symboliserar också diskurser om den sjuka och döende kroppen som i hög grad kopplad till skam och förlust av kontroll och en önskan från sjukvården om att i högsta möjliga mån kontrollera denna och när det är möjligt undanhålla den från det offentliga. Som Lawton skriver blir hospice en plats där patientens kropp ska omvandlas från 'unbounded' till 'bounded' och där symptomen, vilka får ytan på patientens kropp att rämna och brytas ned, ska kontrolleras (Lawton, 1998). Den gränslösa kroppen blir något som ska avgränsas från det övriga samhället och därigenom skapas idéer om den levande kroppen som hygienisk och sanerad.…”
Section: Tiden Kvar: Döden Kommer Närmareunclassified
“…Vårdinstitutioner handlar inte bara om att vårda de som är sjuka, utan också om att dela upp befolkningar i normala och patologiska, friska och "hög-risk" (exempelvis som vi sett tidigare i texten i relation till hiv). Detta resulterar i upprättandet av gränser, där de som är sjuka snarare än att läkas ska sorteras ut som queera bort från den mytologiserade friska familjen (Lawton, 1998;Bost, 2008:347). Lawton menar att hospice och liknande institutioner finns för att hålla kroppars förfall, nedbrytning och döende skilda från resten av samhället, men också för att de ska återta kontrollen över kroppen och återupprätta dess gränser och att de möjliggör vissa idéer om den hygieniserade, sanitära och somatiskt bundna kroppen symboliskt bevarade.…”
Section: Tiden Kvar: Döden Kommer Närmareunclassified
See 1 more Smart Citation